ANALISIS VISUAL DESAIN VIDEO GAME SUPER MARIO BROS. TAHUN 1985 - Mileneo Prayudyanto; Evelyne Henny Lukitasari; Ahmad Khoirul Anwar (Akademi Seni dan Desain Indonesia Surakarta, 2024)
This article discusses the results of research on the visual design elements and design principles used in the Super Mario Bros. video game. 1985. These two things are reflected in the problem formulation, namely looking for what visual design elements and design principles are used in the video game. Meanwhile, the aim of this research is to find the answers listed in the two problem formulations above. The research method used was descriptive qualitative with primary data, namely the video game itself and secondary by distributing questionnaires or surveys. The result of the research obtained was that Super Mario Bros., released in 1985 for the Nintendo Entertainment System (NES), utilized various visual design elements, including lines, shapes, textures, and colors, to create an iconic and memorable game world. In this research it was found that in the video game Super Mario Bros. 1985 there are several classifications of lines (horizontal and vertical) such as ground lines, block lines, pipe lines, platform lines, enemy lines, and scenery lines. As for shape, various shapes or planes are found in the characters and the number of pixels that make up the characters in the video game. Other design elements are the textures found in solid block textures, ground, backgrounds, and enemies. Meanwhile, Super Mario Bros. 1985 uses a limited color palette, and specific RGB percentages for background colors may not be available or well documented. For the design principles used in the video game Super Mario Bros. 1985 are emphasis, balance, rhythm and unity. Each character, both protagonist and antagonist, has unique characteristics in their design principles. Likewise, for other supporting elements, they have unique characteristics in their design principles. Finally, as a reinforcement of the findings of the design principles used in Super Mario Bros. 1985, a survey (15 questions) was conducted on 52 people and those who answered the survey were 37 people who were respondents with experience of playing this video game. Keywords: visual elements, design principles, Super Mario Bros. 1985